(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the morbimortality profile of amebiasis and its relationship with basic sanitation indicators in Brazil, between 2010 and 2021. Methods: A descriptive study of the profile of morbidity and mortality due to amebiasis and socioeconomic characteristics and sanitation indicators, between 2010 and 2021. Results: We observed an hospitalization rate with a decreasing trend from 1.7/100mil (2010) to 0.3/100mil (2021); and mortality rate of 0.05/100mil (2010) and 0.02/100mil (2019), with higher records in the North and Northeast, especially Pará (103.2/100mil) and Maranhão (102.2/100mil) for hospitalization and Acre (3.1/100mil) for mortality; for socioeconomic and sanitation aspects, the worst scenario was in the states of the North and Northeast with low income, poor sanitation conditions, low coverage of health insurance and schooling, and incipient hygiene habits in all states of Brazil. The profile of hospitalizations was prevalent in women (50.7%), between 1 and 14 years (34.7%), with emergency care (83.8%); for deaths, men (52.5%), >70 years (44.2%), prevailed. Conclusion: Based on the findings, we can infer a relationship between the worst socioeconomic indicators and sanitation and hospitalizations and deaths due to amebiasis, especially in the North and Northeast, favoring the maintenance of occurrences.